Hedge Fund Intervention and Accounting Conservatism - Cheng, C.S. Agnes; Huang, Henry He; Li, Yinghua (Contemporary Accounting Research, 2015)
Abstract Hedge fund intervention has been associated with many positive corporate changes and is an important vehicle for informed shareholder monitoring. Effective monitoring has also been positively associated with accounting conservatism. Building upon these prior results, we predict an increase in accounting conservatism after hedge fund intervention. We use a large sample of hedge fund activist events and identify control firms with similar likelihoods of being targeted using the propensity score matching method to apply difference‐in‐difference tests. We find that when hedge fund activists have relatively large ownership and sufficient time to exert their monitoring power, target firms experience significant increases in conditional conservatism. CFO turnovers, upward/lateral auditor switches, and improvements in audit committee independence after intervention are accompanied by greater increases in conditional conservatism. Finally, we find greater increases in conditional conservatism when there is a lack of monitoring by dedicated institutional investors before the intervention. Our study suggests that hedge fund activists improve accounting monitoring tools and thus adds important new evidence on the effectiveness of shareholder monitoring on accounting practices.